2014
DOI: 10.1245/s10434-014-4196-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved Long-Term Outcomes After Resection of Pancreatic Adenocarcinoma: A Comparison Between Two Time Periods

Abstract: Factors associated with improved long-term survival remain comparable over time. Short- and long-term survival for patients with resected PDAC has improved over time due to decreased perioperative mortality and increased use of adjuvant therapy, although the proportion of 5-year survivors remains small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…As expected, the overall R0 resection rates reported in our review (70–77 %) are slightly lower, as reported by two recent studies (84–92 %) on borderline resectable disease 24,25. Surgical outcomes post-resection seem comparable with outcomes in upfront resectable patients, although still based on immature data 2628…”
Section: Discussionsupporting
confidence: 83%
“…As expected, the overall R0 resection rates reported in our review (70–77 %) are slightly lower, as reported by two recent studies (84–92 %) on borderline resectable disease 24,25. Surgical outcomes post-resection seem comparable with outcomes in upfront resectable patients, although still based on immature data 2628…”
Section: Discussionsupporting
confidence: 83%
“…1 Surgical resection is the only curative treatment option for pancreatic cancer patients with a 5-year survival of 20–25 %. 2,3 While the mortality associated with pancreatic resection has dramatically decreased over the last several decades, morbidity remains a problem. 46 Specifically, up to 20–40 % of patients will experience some type of complication following pancreatic resection.…”
Section: Introductionmentioning
confidence: 99%
“…Those findings imply medical practice variation attributable to institution-specific practice patterns, both in terms of patients receiving adjuvant treatment compared with obs, and in terms of patients receiving ctx compared with crt. Indeed, a recent analysis of pcc treatment at a single Ontario institution noted the prevailing historical practice of not referring patients for adjuvant radiation, possibly relating to the publication of evidence supporting the role of ctx alone during the study period 5,22,24,25 . Such referral patterns and institutional biases might partly underlie the observed geographic variation in rates and types of adjuvant treatment administered.…”
Section: Discussionmentioning
confidence: 99%